2008
DOI: 10.1007/s12078-008-9006-4
|View full text |Cite
|
Sign up to set email alerts
|

A Role of the Epithelial Sodium Channel in Human Salt Taste Transduction?

Abstract: Mammals perceive the five different taste qualities: bitter, sweet, umami, sour, and salty. At least two different mechanisms contribute to salt taste in rodents. One is elicited by various cations and sensitive to cetylpyridinium chloride, whereas another is selectively stimulated by Na + and inhibited by amiloride. The latter pathway has been suggested to involve the epithelial sodium channel, ENaC. In humans, the presence of amiloride-sensitive salt taste transduction is being disputed. In this paper, we ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 53 publications
1
52
2
1
Order By: Relevance
“…Another sensing system is activated by lower concentrations of Na + and inhibited by amiloride, suggesting the contribution of ENaC in salt taste. In humans, a, b, g, and d ENaC subunits are expressed in taste bud cells (Stahler et al, 2008). In mice lacking a ENaC in taste receptor cells, the highly sensitive response to Na + salt and the behavioral attraction to sodium salt were considerably reduced (Chandrashekar et al, 2010).…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 99%
“…Another sensing system is activated by lower concentrations of Na + and inhibited by amiloride, suggesting the contribution of ENaC in salt taste. In humans, a, b, g, and d ENaC subunits are expressed in taste bud cells (Stahler et al, 2008). In mice lacking a ENaC in taste receptor cells, the highly sensitive response to Na + salt and the behavioral attraction to sodium salt were considerably reduced (Chandrashekar et al, 2010).…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 99%
“…112 Evolutionary forces may have shaped the human ability to recognize salty taste in such a way as to make it very responsive to differences in the environmental mineral and water supply or habitual diet. 113 Therefore, efforts to assess the impact of genetic variation within the salt receptor 114,115 should focus on salt perception of people with similar environmental backgrounds (e.g., early exposure, recent exposure) and be attentive to the current state of the subject (e.g., time of day, thirst).…”
Section: Salt As a Simple Pleasure And Complex Poisonmentioning
confidence: 99%
“…The sodium channel epithelial Na + channel (ENaC) and its subunits are implicated in salt perception in mice and rats [76], but the evidence supporting the involvement of this gene and its protein products in human salt perception is equivocal [77]. Genetic studies of threshold for sodium chloride suggest little genetic involvement [74,78], but studies of intensity ratings of concentrated solutions have shown a moderate degree of heritability (Knaapila et al, submitted).…”
Section: Differences In Umami Sour and Salty Taste Detectionmentioning
confidence: 99%